Studies on muscle residues of the anti-bacterial veterinary medicines tilmicosin, enrofloxacin and tiamulin in livestock and the risk to consumers from ingestion of injection-sites - Beechinor, Jeremiah Gabriel (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2001)
Studies on incurred residues of the veterinary anti-bacterials tilmicosin, enrofloxacin and tiamulin were undertaken in cattle, sheep and pigs in order to investigate the effects of cooking on injection-site residues and to evaluate their potential hazards for public health. The studies also included a survey of more than 2500 blemishes in primal and subprimal portions of Irish beef, mutton and pork which provided information both on the extent of tissue damage and on the prevalence of residues of anti-bacterials at these sites.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin